Determinants of Helping Behaviour among Community-Based Disaster Volunteers in Yogyakarta - Arianti, Nevi Kurnia; Koentjoro, Koentjoro; Muhammad, Baiquni (TDMRC, Universitas Syiah Kuala, 2024)
Since community-based disaster volunteers are the backbone of effective disaster preparedness programs, their helpful behavior is crucial in disaster-prone areas. The delivery of psychosocial support will be streamlined if volunteers' helpful conduct is understood. The purpose of this study is to determine the acceptability of the suggested volunteer helpful behavior model. Altruism and egoism-helping behavior are the study's endogenous variables. Social and personal norms, the degree of dependence, and the length of time spent volunteering are the exogenous variables. To address the research questions, a survey-based quantitative study was carried out. 292 community-based volunteers in the Yogyakarta Special Region Province, ages 20 to 61, participated in the survey. Covariance-based structural equation modeling (CB-SEM) was employed for data analysis. Maximum Likelihood Robust (MLR) is the estimate that is employed to overcome anomalous data. The model fits the data, according to the model accuracy index. The analysis's findings indicate that altruism helping behavior is influenced by personal norms and dependency level, and egoism helping behavior is influenced by social norms and dependency level. Implications of the study results: Building volunteer capacity must focus on enhancing society values, personal values, and circumstances enabling help such as standardized physical equipment, knowledge, and abilities.